CRIMINOLOGY ANALYSIS OF CERTAIN MODERN DETERMINANTS OF TRANSNATIONAL ORGANIZED CRIME (Bulletin of criminological association of Ukraine, 2025)
The article is devoted to the determinants of transnational organized crime. The main types of criminogenic factors contributing to the emergence and activity of transnational organized criminal groups are considered. The author analyzes them and provides a brief description of the main types of determinants of criminal activity in terms of its content, such as: economic factors, political factors, social factors, technological factors, geographical and demographic factors.
Keywords: organized crime; transnational organized crime; determinants; criminal activity